Neutron activation analysis of samples from the Kimberley Reef Conglomerate - Rasmussen, Stephen Eric (My University, 2015)
The technique of instrumental neutron activation analysis as applied to the analysis cf geological material has beer siudiel with particular emphasis on methods of reducing or eliminating analytical errors. The neutron flux gradients in the reactor irradiation facilities used were found to introduce errors of up to 20%. The use of iron foils to monitor both the thermal and fast neutron flux received by individual samples has been shown to reduce iiradiation errors to approximately 1%. The contribution of epithermal neutron resonances to (n, >’ ) reaction cross sections has been recognised. Estimated epithermal neutron flux factors have been shown to reduce the associated errors by as much as 7%.
Keywords: Geochemistry.